AKIBAT HUKUM TERHADAP TINDAKAN DIREKSI DAN DEWAN KOMISARIS PERSEROAN TERBATAS YANG TELAH BERAKHIR MASA JABATANNYA DAN TIDAK DISAHKAN OLEH RAPAT UMUM PEMEGANG SAHAM - GUNAWATI GUNAWATI (PREMISE LAW JURNAL, 2018)
Dosen Pembimbing:1. Prof. Dr. Sunarmi, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Tony, SH, MKnMembers of the Board of Directors and the Board of Commissioners are limited company organs appointed for a certain period of time and can be reappointed, based on Article 94, paragraph 3 and Article 111, paragraph 3 of Law No. 40/2007 on Limited Liability Company. The research problems are how about the legal consequence of the action of the management of a limited liability company whose tenure has ended and is not validated by RUPS (General Shareholders’ Meeting), how about a Notary’s liability in making his Deed when the company’s management’s tenure has ended, and how about the legal solution for the management whose tenure has ended according to Law No. 40/2007 in Limited Liability Company. The research used juridical normative method. It also used the combination of Statute Approach and Case Approach.Keywords: Board of Directors and Board of Commissioners, Tenure, Notary’s Liability, Appointment of Management